Discovery of a New Class of Immunosuppressants fromTrichothecium roseumCo-inspired by Cross-Kingdom Similarity in Innate Immunity and Pharmacophore Motif - Zhang, Ai Hua; Wang, Xing Qi; Han, Wen Bo; Sun, Yang; Guo, Ye; Wu, Qi; Ge, Hui Ming; Song, Yong Chun; Ng, Seik Weng; Xu, Qiang; Tan, Ren Xiang (Wiley, 2013)
The limited selection of immunosuppressants in the clinic hampers the efficient management of immune disorders such as rejections after organ transplantations. However, the search for new immunosuppressive compounds remains random and creates inevitably financial and laborious wastes. Herein, we present an immunity-inspired discovery strategy that rationally allows an efficient identification of immunosuppressive compounds from the endophyte culture, as exemplified by the new peptide trichomide A. This compound exerts its immunosuppressive action more selectively than cyclosporin A. It was found that trichomide A decreases the expression of Bcl-2, increases the expression of Bax, and has a small or negligible effect on the expressions of p-Akt, CD25, and CD69. Our study strengthens the idea that the cross-kingdom similarity in immunity among living things could provide a shorter route towards the identification of natural products valuable for the development of new immunosuppressants. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.